Transparansi dan Pengawasan Keuangan Negara dalam Implementasi Program Makan Bergizi Gratis (MBG) - Bening Tirta Wibowo; Friski Ardeka Sahda Rianestu; Indra Devian Lumban Gaol (Jurnal Media Administrasi, 2026)
As a priority program that utilizes a large portion of the state budget in its implementation, the Free Nutritious Meals (MBG) program that requires transparent and accountable financial management. This study examines transparency and state financial oversight in the implementation of the Free Nutritious Meals Program. It employs a qualitative approach based on a literature review of various policy sources, government reports, and relevant news coverage. The results of the analysis indicate that the government has made efforts to strengthen governance through the development of digital reporting mechanisms and by enhancing the capacity of program implementers via e-learning systems and financial reporting applications for a partners of the Nutrition Service Units (SPPG). Strengthening and greater transparency of information regarding the allocation and implementation of the program’s budget are needed to ensure public access, thereby realizing transparent and accountable public financial management in the implementation of the Free Nutritious Meals Program.